PROFESIONALISME DAN KINERJA PEGAWAI KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Ade Hermawan; M. Faisal Rizal (Universitas Tribhuwana Tunggadewi, 2019)
Government Employees of Liang Anggang District, show the profesionalism in duties. The result shown by three indicators that researchers use as a measurement to assess the professionalism of Government Employees. The Government Employees have work ability, full skills, and work experience. The Government Employees also have good productivity. In addition the researcher found that Government Employees also have good acievement, including quality, quantity, and finishing the duties.